Optimal placement and design of M-STLCDs in n-story buildings: a comparative study with M-TMDs and M-TLCDs - Masnata, Chiara; Di Trapani, Salvatore Dario; Russotto, Salvatore; Pirrotta, Antonina (Frontiers in Built Environment, 2025)
This study proposes a novel optimization procedure for the seismic vibration control of multi-degree-of-freedom systems incorporating Multiple Sliding Tuned Liquid Column Dampers (M-STLCDs). Unlike conventional compliant liquid-based devices, the proposed system consists of multiple translating U-shaped liquid containers, each independently tuned to a specific structural mode, enabling multi-modal control, particularly suited for stiff structures and not previously explored in the literature. The procedure can optimize and install one device at a time while accounting for the modifications introduced by prior installations, ensuring a progressive adaptation of the control system to the dynamic characteristics of the structure. For each single STLCD, the procedure considers both the optimal location in the building and the fundamental mode to be controlled. More specifically, for each STLCD, the procedure detects the optimal floor where the device should be placed and optimizes the damping and the natural frequency of the spring-dashpot unit, the head-loss coefficient and the natural frequency characterizing the liquid. To prove the effectiveness of the optimal placement of the devices, the optimization procedure was applied on two different types of shear-type structures, i.e., on a three-story and a six-story structure, subjected to a broadband and zero-mean white noise process. Moreover, the control performance of the device was evaluated both in the time and the frequency domain and under recorded seismic events, in comparison with optimized configurations of traditional devices, such as Multiple Tuned Mass Dampers (M-TMDs) and Multiple Tuned Liquid Column Dampers (M-TLCDs).